KOMUNIKASI POPULIS ANIES BASWEDAN DI MEDIA SOSIAL - Mubarok, Erick Saepul; Handoko, MP (Virtu: Jurnal Kajian Komunikasi, Budaya dan Islam, 2024)
This study aims to analyze the populist communication of Anies Baswedan before the presidential candidate determination by the KPU, through the content on his Instagram account @aniesbaswedan. This research employs a qualitative content analysis method on 42 posts uploaded during the period from June 11 to July 10, 2022. The findings indicate that Anies Baswedan uses a populist communication strategy by prioritizing the people's interests, advocating for the people, and indirectly criticizing the elite. The uploaded content includes photo collages, images, and videos with narratives depicting closeness to the public and populist issues. This communication style effectively increases user engagement on Instagram, with the highest engagement achieved through photo collage content. In conclusion, the populist communication employed by Anies Baswedan on Instagram plays a significant role in building public image and support in the 2024 Presidential Election. Populist Communication, Anies Baswedan, Social Media, Instagram